The effect of pH on Marinobacter hydrocarbonoclasticus denitrification pathway and nitrous oxide reductase - Carreira, Cíntia (2020)
PTDC/BBB-BQB/0129/2014 (IM). This work was supported by the Applied Molecular Biosciences Unit-UCIBIO, and Associate Laboratory for Green Chemistry-LAQV, which is financed by national funds from FCT (UIDB/04378/2020 and UIDB/50006/2020, respectively).